2017
DOI: 10.1111/1541-4329.12122
|View full text |Cite
|
Sign up to set email alerts
|

Development, Dissemination, and Assessment of a Food Safety Systems Management Curriculum for Agribusiness Students in Armenia

Abstract: This study addresses the development, dissemination, and assessment of a Food Safety System Management (FSSM) curriculum offered to college-aged, agribusiness students in Yerevan, Armenia. Prior to beginning the program, demographic data were collected and a paper-based pretest was administered to access the food safety knowledge, behavior, and attitude of participants (n = 29). For assessment of a skill, participants' handwashing techniques were videotaped and scored before the program commenced. Immediately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…It was also found that the participants’ knowledge level was maintained 6 months after FSSC program ( p ≥ .05). These findings are consistent with a similar study (Pokharel et al., 2017) and also were observed when food safety training programs were conducted for food handlers and quick service employees (Costello, Gaddis, Tamplin, & Morris, 1997: Mclntyre, Vallaster, Wilcott, Henderson, & Kosatsky, 2013).…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…It was also found that the participants’ knowledge level was maintained 6 months after FSSC program ( p ≥ .05). These findings are consistent with a similar study (Pokharel et al., 2017) and also were observed when food safety training programs were conducted for food handlers and quick service employees (Costello, Gaddis, Tamplin, & Morris, 1997: Mclntyre, Vallaster, Wilcott, Henderson, & Kosatsky, 2013).…”
Section: Resultssupporting
confidence: 91%
“…As a result of the delivery of FSSC curriculum, it was observed that most of the participants changed their attitudes toward proper general food safety practices and safe food handling (Table 3) and mirrors previous research (Pokharel et al., 2017). Participants changed behavior in the following areas: checking the expiration date before buying foods, not eating raw meat products, using different cutting boards for different food commodities, the importance of food safety‐related trainings, and their general interest in future trainings.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations